Stock prices and long-run demand for money in three selected ASEAN countries : Indonesia, Malaysia, and Thailand - Tan, Chin Sin (2003)
Earlier study on money demand has omitted the influence of stock prices in the domestic demand for money especially in ASEAN countries. This paper investigates the relationship between stock prices and the long-run money demand function in Indonesia, Malaysia and Thailand using the multivariate cointegration and error correction model methodology. Results show that stock prices playa significant role in the determination of stationary long-run real M2 demand function in those countries. The direction and magnitude of the role of stock price depends upon the country and also the sampling period included. The results from the vector error correction model (VECM) provide evidence of causality between the real money stock and the determinants of the money demand (including real stock prices).